Publication Strategy For Introducing The Batujaya Karawang Temple Complex in The Webtoon Design “Unur Batu” - Aidha Rohmalia; Muhammad Fauzi (TEXTURE Art and Culture Journal, 2025)
Most people in Indonesia do not know that the oldest temple in Indonesia is in Karawang Regency. The design of the Webtoon "Unur Batu" was made with the hope that it can be an educational material that introduces the public to the Temple Complex in Batujaya, Karawang Regency. The typography on the narration and sound effects uses the Lafayette Comic Pro, Badaboom BB, and BD Cartoon Shout fonts, while the typography on the logo uses the Know Your Product font. The promotional strategies used include video reels and printed promotional media in the form of merchandise.